Unravelling of a mechanism of resistance to colistin in Klebsiella pneumoniae using atomic force microscopy. (27th May 2015) - Formosa, C.; Herold, M.; Vidaillac, C.; Duval, R. E.; Dague, E.
Abstract: Objectives: In this study we focused on the mechanism of colistin resistance in Klebsiella pneumoniae . Methods: We used two strains of K. pneumoniae : a colistin-susceptible strain ( K. pneumoniae ATCC 700603, KpATCC) and its colistin-resistant derivative (KpATCCm, MIC of colistin 16 mg/L). We performed a genotypic analysis based on the expression of genes involved in LPS synthesis and L-Ara4N moiety addition. We also explored the status of the mgrB gene. Then, a phenotypic analysis was performed using atomic force microscopy (AFM). The Young modulus was extracted from force curves fitted using the Hertz model, and stiffness values were extracted from force curves fitted using the Hooke model. Results: We failed to observe any variation in the expression of genes implicated in LPS synthesis or L-Ara4N moiety addition in KpATCCm, in the absence of colistin or under colistin pressure (versus KpATCC). This led us to identify an insertional inactivation/mutation in the mgrB gene of KpATCCm. In addition, morphology results obtained by AFM showed that colistin removed the capsule from the susceptible strain, but not from the resistant strain. Nanomechanical data on the resistant strain showed that colistin increased the Young modulus of the capsule. Extend force curves recorded on top of the cells allowed us to make the following hypothesis about the nanoarchitecture of the capsule of the two strains: KpATCC has a soft capsule consisting of one layer, whereas the KpATCCm capsule is harder and organized in several layers. Conclusions: We hypothesize that capsular polysaccharides might be implicated in the mechanism of colistin resistance in K. pneumoniae, depending on its genotype.